Hesperetin and it nanocrystals ameliorate social behavior deficits and oxido-inflammatory stress in rat model of autism. Issue 69 (October 2018) - Khalaj, Rashin; Hajizadeh Moghaddam, Akbar; Zare, Mahboobeh
Highlights: Prenatal injection of VPA not only induces anxiogenic-like behavior but also remarkable decrease in social interaction, increased repetitive behavior and oxido-inflammatory stress. Mother administration of Hst and nano-Hst can ameliorate autistic-like behaviors and oxido-inflammatory parameters in animal model of autism based on prenatal exposure to VPA. Histopathological ﬁndings suggests that Hst and nano-Hst protected Purkinje cells of cerebellum in animal model of autism. Abstract: Prenatal exposure to valproic acid (VPA) induces behavioral disorders and enhancement of oxido-inflammatory stress in Autism Spectrum Disorders (ASDs). The aim of this study was to investigate the comparative effects of hesperetin (Hst) and nano-hesperetin on social behavior deficits and oxido-inflammatory indexes in prenatally valproic acid-exposed rat offspring. Pregnant Wistar rats on embryonic day 0 (E0) were segregated into six groups; Group-1 served as vehicle, received distillated water orally (PO) from E1 until the end of lactation and saline intraperitoneally (i.p) on E12.5. Group-2 received sodium valproate (500 mg/kg in 0.9% saline, i.p) on E12.5 was considered as VPA-exposed group, Group-3 to 6 were VPA-exposed which received hesperetin and nano-hesperetin (10 and 20 mg/kg/day, PO) from E0 until the end of lactation respectively. Social interaction and open field tests were conducted on postnatal day 28 (PND 28) and PND 30, cerebral antioxidant enzymes activity and biochemical indexes, the level of inflammatory factors in plasma and histopathology of cerebellum were estimated on PND 28 and PND 30. Prenatal valproic acid-exposed rat exhibited poor sociability and high level of anxiety-like behaviors ( P < 0.05). In addition, increased level of oxidative stress and inflammation were found by determining different oxido-inflammatory markers. Hesperetin and nano-hesperetin treatment improved the behavioral disorder and reduced the oxidative stress in brain and significantly (p < 0.05) plasma's inflammation indexes. In conclusion, it can be state that nano-hesperetin exerts neuroprotective action in comparison with hesperetin and could be efficacious for treatment of VPA animal model of autism during pregnancy and lactation.